1998
DOI: 10.1093/emboj/17.23.7078
|View full text |Cite
|
Sign up to set email alerts
|

Nhp2p and Nop10p are essential for the function of H/ACA snoRNPs

Abstract: The small nucleolar ribonucleoprotein particles containing H/ACA-type snoRNAs (H/ACA snoRNPs) are crucial trans-acting factors intervening in eukaryotic ribosome biogenesis. Most of these particles generate the site-specific pseudouridylation of rRNAs while a subset are required for 18S rRNA synthesis. To understand in detail how these particles carry out these functions, all of their protein components have to be characterized. For that purpose, we have affinitypurified complexes containing epitope-tagged Gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
255
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(268 citation statements)
references
References 82 publications
9
255
0
3
Order By: Relevance
“…These proteins were ®rst identi®ed in budding yeast as Gar1p, Cbf5p, Nhp2p and Nop10p (Girard et al, 1992;Balakin et al, 1996;Ganot et al, 1997;Lafontaine et al, 1998;Watkins et al, 1998;Henras et al, 1998). Loss of expression of any one of these proteins results in growth arrest with aberrant rRNA, and loss of any one except Gar1p prevents the accumulation of H/ACA snoRNAs.…”
Section: Rna Accumulationmentioning
confidence: 99%
“…These proteins were ®rst identi®ed in budding yeast as Gar1p, Cbf5p, Nhp2p and Nop10p (Girard et al, 1992;Balakin et al, 1996;Ganot et al, 1997;Lafontaine et al, 1998;Watkins et al, 1998;Henras et al, 1998). Loss of expression of any one of these proteins results in growth arrest with aberrant rRNA, and loss of any one except Gar1p prevents the accumulation of H/ACA snoRNAs.…”
Section: Rna Accumulationmentioning
confidence: 99%
“…Similar to other H/ACA RNAs, human telomerase RNA is stabilized by the H/ACA core proteins (Mitchell et al 1999;Dragon et al 2000;Dez et al 2001). Genetic depletion studies in yeast demonstrated that all H/ACA core proteins, except GAR1, are essential for the stability of H/ACA RNAs (BousquetAntonelli et al 1997;Henras et al 1998;Lafontaine et al 1998;Watkins et al 1998). Nevertheless, X-DC mutations have only been identified in NAP57 but none of the other core proteins (Marrone and Mason 2003).…”
Section: Protein Dynamics Of H/aca Rnpsmentioning
confidence: 99%
“…This is based on the following three observations. First, all core proteins, except GAR1, are essential for the stabilization of all H/ACA RNAs (Bousquet-Antonelli et al 1997;Henras et al 1998;Lafontaine et al 1998;Watkins et al 1998;Dez et al 2001). Second, all H/ACA RNPs can be precipitated with antibodies directed against any of the core proteins, including GAR1 (Balakin et al 1996;Ganot et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The protein core of the box C/D snoRNP is composed of Nop1p, Nop58p, Nop56p, and Snu13p (9, 10) with Nop1p as the candidate methyltransferase (2). The core of the box H/ACA snoRNP contains four proteins, Gar1p, Nhp2p, Nop10p, and Cbf5p, which is presumably responsible for the pseudouridyl synthetase activity (4,(11)(12)(13)(14)(15). Although the RNA motifs required for the association of the snoRNP proteins with the box H/ACA snoRNAs have been investigated (16,17), little is known about the mechanisms by which the RNA and the protein components become assembled into mature snoRNPs.…”
mentioning
confidence: 99%
“…A few independently transcribed box H/ACA snoRNAs also undergo 5Ј end processing by the double-stranded RNA endonuclease Rnt1p (19). The packaging of box H/ACA snoRNAs into snoRNPs is likely to occur at an early stage of biogenesis, since unprocessed snoRNA precursor accumulation requires the presence of the box H/ACA snoRNPs Nhp2p and Nop10p (13). After or during the course of the maturation of the snoRNAs, the snoRNPs are exported to the nucleolar compartment to function in ribosomal RNA processing and/or modification.…”
mentioning
confidence: 99%